Jesus' Last Week : Jerusalem Studies in the Synoptic Gospels - Volume One - Notley, R. Steven,; Turnage, Marc,; Becker, Brian, (Jewish and Christian Perspectives Series;, 2006)
For the past forty years, but for only the first time in history, Christian scholars fluent in Hebrew and living in the land of Israel have collaborated with Jewish scholars to examine Jesus' sayings from a Judaic and Hebraic perspective. The result of this research confirms that Jesus was an organic part of the diverse social and religious landscape of Second Temple-period Judaism. He, like other Jewish sages of his time, used specialized methods to teach foundational Jewish theological concepts such as God's abundant grace. Jesus' teaching was revolutionary in a number of ways, particularly in three areas: his radical interpretation of the biblical commandment of mutual love; his call for a new morality; and his idea of the Kingdom of Heaven. Jerusalem Studies in the Synoptic Gospels , the initial volume, focuses on the Passion Narratives in a search for the Historical Jesus. It also reexamines the synoptic problem in light of recent historical and archaeological research. The volume represents the first attempt by members and associates of the Jerusalem School to apply collectively the methodology pioneered by Robert Lindsey and David Flusser. Included in the volume is the final article written by the late Professor Flusser, The Synagogue and the Church in the Synoptic Gospels.